Extraocular Surgical Approach for Placement of Subretinal Implants in Blind Patients: Lessons from Cochlear-Implants - Assen Koitschev; Katarina Stingl; Karl Ulrich Bartz-Schmidt; Angelika Braun; Florian Gekeler; Udo Greppmaier; Helmut Sachs; Tobias Peters; Barbara Wilhelm; Eberhart Zrenner; Dorothea Besch (Journal of Ophthalmology)
In hereditary retinal diseases photoreceptors progressively degenerate, often causing blindness without therapy being available. Newly developed subretinal implants can substitute functions of photoreceptors. Retina implant extraocular surgical technique relies strongly on cochlear-implant know-how. However, a completely new surgical approach providing safe handling of the photosensor array had to be developed. The Retina Implant Alpha IMS consisting of a subretinal microphotodiode array and cable linked to a cochlear-implant-like ceramic housing was introduced via a retroauricular incision through a subperiosteal tunnel above the zygoma into the orbit using a specially designed trocar. Implant housing was fixed in a bony bed within a tight subperiosteal pocket in all patients. Primary outcomes were patient short term safety as well as effectiveness. Nine patients participated in the first part of the multicenter trial and received the subretinal visual implant in one eye. In all cases microphotodiode array pull-through procedure and stable positioning were possible without affecting the device function. No intraoperative complications were encountered. The minimally invasive suprazygomatic tunneling technique for the sensor unit as well as a subperiosteal pocket fixation of the implant housing provides a safe extraocular implantation approach of a subretinal device with a transcutaneous extracorporeal power supply.